Pengaruh Media Pembelajaran Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Matematika di Sekolah Dasar - Ade Mustika Andari; Zubaidah Amir; R. Risnawati; Mhmd Habibi (Universitas Sarjanawiyata Tamansiswa, 2023)
Growing student motivation is one of the techniques in developing the ability and willingness to learn. The purpose of this study was to determine the effect of instructional media on students' learning motivation in mathematics in elementary schools. This type of research is